Centro de Rehabilitación y Consumo Supervisado de Drogas (2022)
In this work is the approach of a rehabilitation center for the city of Ibagué - Tolima; it is based on the collection of data, samples of consumers and types of drugs that they ingest in the city; also in the possible solutions offered by public entities, government laws, rehabilitation manuals, neighborhood leaders, ordinary people and even consumers themselves. Due investigations are made regarding the consumption of psychoactive substances in Ibagué, additionally a field study was carried out to find out how many help points, rehabilitation centers or foundations exist in the city, the types of procedures that are used with patients.